THEORETICAL BASIS OF THE FORMATION OF FINANCIAL RESULTS IN THE COTTON-TEXTILE CLUSTER (American Journal of Business Management, Economics and Banking, 2024)
The theoretical basis of the formation of financial results in the cotton-textile cluster is considered. The process of origination of income and expenses from enterprise activity has been studied. The trends of the added value chain in cotton-textile clusters and the level of coverage of the added value chain in cotton-textile clusters operating in Uzbekistan were analyzed.